Regional disparities in health care resources in traditional Chinese medicine county hospitals in China - Zhu, Dawei (PLoS One, 2020)
OBJECTIVE: We aimed to analyze regional disparities of health care resources in traditional Chinese medicine (TCM) county hospitals and their time trends, and to assess the changes of regional disparities before and after 2009 health care reforms. METHODS: We used hospital-based, longitudinal data from all TCM county hospitals in China between 2004 and 2016. To measure the key development features of TCM county hospitals, data were collected on government hospital investment, hospital numbers (the average number of TCM hospitals per county), hospital scale (the number of medical staff and hospital beds) and doctors’ workload (the daily visits and inpatient stays per doctor). We used segmented linear regression to test the time trend for outcome variables. We set a breakpoint at 2011, dividing the pre-reform (2004–2011) and post-reform (2012–2016) periods. RESULTS: After the 2009 health reforms, TCM hospitals continued to display large disparities in the number, scale, and doctors’ workload across the three regions. In the pre-reform period, yearly government subsidies for TCM hospitals in western area were roughly RMB0.6 million (US$89 thousand) more than those in central and eastern region, which increased under the 2009 reforms to roughly RMB2 million (US$298 thousand) more per yer in post-reform period. These increased subsidies saw an increase in the number of TCM hospitals in the western area, partly addressing regional disparities. But there was no improvement in the regional disparities in terms of scale (number of beds) and the doctors’ workload (daily outpatient visits and inpatients per doctor) increased or remained unchanged between the western and other regions. CONCLUSION: Although TCM hospital number, scale, and doctors’ workload increased over the past 13 years, substantial regional disparities remained. The 2009 health reforms did not significantly change the regional disparities in health care resources, especially between the eastern and western regions.